Identifying Cancer-Directed Surgeries in Medicare Claims: A Validation Study Using SEER-Medicare Data - Lavery, Jessica A. (JCO Clin Cancer Inform, 2019)
PURPOSE: Medicare claims provide a rich data source for large-scale quality assessment because data are available for all beneficiaries nationally. For cancer surgery, the absence of information regarding site of cancer and date of diagnosis on an administrative claim necessitates testing to ensure accurate quality assessment and public reporting. METHODS: Using the SEER Medicare–linked database as the gold standard, we developed and tested an approach to identify cancer-directed surgeries from Medicare fee-for-service claims alone. Our analysis evaluated two questions: (1) Can we identify a large percentage of patients who underwent a cancer-directed surgery using only Medicare claims? (2) Of all patients identified as having undergone a cancer-directed surgery, what percentage had cancer? We evaluated this approach for 17 primary cancer sites. RESULTS: The number of Medicare beneficiaries diagnosed with their first cancer during the years 2011 to 2013 and who underwent cancer-directed surgery ranged from 45 patients (bones and joints) to 20,163 patients (breast). The percentage of cancer-directed surgeries identified using Medicare claims alone ranged from 62% (skin melanoma) to 94% (prostate). For all but three cancer sites (skin melanoma, thyroid, and urinary bladder), more than 80% of cancer-directed surgeries were identified using our approach. Of all surgeries identified, more than 90% were for patients with cancer. CONCLUSION: Identifying patients who underwent a cancer-directed surgery from Medicare claims is feasible for many cancer sites, although careful consideration needs to be given to the validity of each site. Our findings support the use of Medicare claims for large-scale quality assessment of cancer surgery by disease site.